Bacterial Diversity and Mycotoxin Reduction During Maize Fermentation (Steeping) for Ogi Production - Okeke, Chiamaka A.; Ezekiel, Chibundu N.; Nwangburuka, Cyril C.; Sulyok, Michael; Ezeamagu, Cajethan O.; Adeleke, Rasheed A.; Dike, Stanley K.; Krska, Rudolf (Frontiers in Microbiology, 2015)
Bacterial diversity and community structure of two maize varieties (white and yellow) during fermentation/steeping for ogi production, and the influence of spontaneous fermentation on mycotoxin reduction in the gruel were studied. A total of 142 bacterial isolates obtained at 24–96h intervals were preliminarily identified by conventional microbiological methods while 60 selected isolates were clustered into 39 OTUs consisting of 15 species, 10 genera and 3 phyla by 16S rRNA sequence analysis. Lactic acid bacteria constituted about 63% of all isolated bacteria and the genus Pediococcus dominated (white maize = 84.8%; yellow maize = 74.4%). Pediococcus acidilactici and Lactobacillus paraplantarum were found at all steeping intervals of white and yellow maize, respectively, while P. claussenii was present only at the climax stage of steeping white maize. In both maize varieties, P. pentosaceus was found at 24–72h. Mycotoxin concentrations (µg/kg) in the unsteeped grains were: white maize (aflatoxin B1 = 0.60; citrinin = 85.8; cyclopiazonic acid = 23.5; fumonisins (B1/B2/B3) = 68.4–483; zearalenone = 3.3) and yellow maize (aflatoxins (B1/B2/M1) = 22.7–513; citrinin = 16,800; cyclopiazonic acid = 247; fumonisins (B1/B2/B3) = 252–1,586; zearalenone = 205). Mycotoxins in both maize varieties were significantly (p<0.05) reduced across steeping periods. This study reports for the first time: (a) the association of L. paraplantarum, P. acidilactici and P. claussenii with ogi production from maize, (b) citrinin occurrence in Nigerian maize and ogi, and (c) aflatoxin M1, citrinin and cyclopiazonic acid degradation/loss due to fermentation in traditional cereal-based fermented food.